Analisis Pemberian Motivasi Dalam Meningkatkan Hasil Belajar Peserta Dewasa Di Bimbingan Belajar Al Khoiriyah - Fariatul Atyasuraya; Aginta Fadilah; Adel Andora (EL-EMIR Institute, 2026)
This study aims to analyze the role of motivation in improving the learning outcomes of adult participants in the Al Khoiriyah tutoring program. This study used a qualitative approach with a descriptive qualitative approach. This approach was chosen to deeply understand the motivational process in improving the learning outcomes of adult participants in the Al Khoiriyah tutoring program, as well as to describe the experiences, perceptions, and changes experienced by participants during the learning activities. The results indicate that motivation plays a crucial role in improving the learning outcomes of adult participants in the Al Khoiriyah tutoring program. Motivation provided through personal attention, positive communication, appreciation for each participant's progress, and reinforcement of spiritual values ​​can build enthusiasm for learning, increase self-confidence, and encourage participants to be more active in the learning process. Observations, interviews, and documentation show changes in participants' learning behavior, such as increased attendance, participation in learning activities, discipline, and commitment to understanding the material being studied.